Topological Quantum Computing: Challenges and Potential - Loso Judijanto; Safiullah Aziz; Omar Khan (Yayasan Adra Karima Hubbi, 2025)
Quantum computing offers great potential for a technological revolution, but challenges related to the stability and resilience of computing systems remain a major obstacle. Topological Quantum Computing (TQC) emerged as one of the solutions to overcome this problem. This study aims to analyze the challenges and potential of TQC in the development of quantum computing that is more stable and resistant to external disturbances. The method used in this study is a literature study by analyzing secondary data from various experiments conducted by leading research institutions. The results show that TQC has the potential to improve the reliability of quantum computing, especially in reducing the error rate that often occurs in conventional quantum systems. Nonetheless, the main challenges faced are the greater scalability and integration issues of the system. The study concludes that despite the promise of TQC, the development of this technology still requires further research to overcome existing technical constraints. The future research direction needs to be focused on the development of topological qubits on a large scale and more efficient integration for practical applications.